STUDY OF CORAL REEF FISH IN RELATION TO LIVE CORAL REEF COVER IN THE TUING MARINE PROTECTED AREA, BANGKA, INDONESIA - Ferizal, Jemi; Supratman, Okto; Adi, Wahyu; Farhaby, Arthur M; Adha, Muhammad Thoriq; Aditia, Tias; Pratama, Juanda Nikolas; Setiadi, Geri (Universitas Mataram, 2025)
Coral reefs play an important role as marine habitat, but are threatened by climate change and human activities. The Tuing Marine Conservation Area, which still has a relatively good coral reef ecosystem, needs to be evaluated to ensure the effectiveness of conservation and support sustainable management. This research evaluates the condition of coral reefs, coral fish biomass and the relationship between coral reefs and coral reef fish in the Tuing Marine Conservation Area located in Tuing Hamlet, Mapur Village, Bangka Regency. Data collection was carried out in March 2024 at three coral reef locations using the underwater photo transect method to observe the percentage of coral cover and the visual census and visual census methods to observe coral reef fish. The average live coral cover is 60.21%, included in the good category. The density of coral fish is 4,905 individuals per hectare with a total of 10 – 14 species. Reef fish biomass is 65.51 kg per hectare. The relationship between coral reefs and coral fish shows that the better the condition of the coral reef, the higher the number of species and biomass of coral fish. These findings highlight the importance of preserving coral reef ecosystems to support biodiversity and sustain fisheries. Conservation efforts should focus on reducing anthropogenic activities, increasing public awareness, and implementing effective management and rehabilitation strategies